(3JSjjQ GdeDSSGJ (B/s - (3MQhT, QajbIs; (3cfGQ, HgjI s ((3GdLRGFQ (B: s (3OGQ GdCeI (B, s, 2021)
(3jVe eONd Edi JMdjd GdeDSSI GdGbJUGOjI, eMjW HjFI GdeDSSI, GdGWGQ GdeaGgjej ddJSjQ, JWhQ GdacQ GdEOGQj, hXGFa GdJSjjQ efG GdJNWjW hGdJNWjW GdESJQGJjLj, GdJfXje hGdgjGcd GdJfXjejI, GdJhLjg, GdQbGHI, EJNGP GdbQGQ, KbGaI GdeDSSI(B.s
(3HjHdjhZQGajG(B: (3U U(B.249-254s
Keywords: (3EOGQI GdCYeGds; (3GdJNWjW GdGSJQGJjLjs; (3GdeDSSGJ GdJLGQjIs